Elemental data for Gonghai Lake sediments show significant effects of human activities on weathering processes after 1550 CE - Jiang, Hong; Han, Yongming; Tang, Yalan; Fan, Huimin; Liu, Bo; Arimoto, Richard (Frontiers in Earth Science, 2023)
The international Anthropocene Working Group has recognized the mid-20th centrury (ca. 1950 CE) as the onset of the Anthropocene, but human activities in China altered the land cover and influenced weathering processes much earlier. Changes in the elemental composition of sediment since 1000 CE form Gonghai Lake were studied, using X-ray Fluorescence element scanning (average time-resolution 3 yr), to investigate the human impacts on weathering over time. We found that Aluminum (Al) and calcium (Ca) containing minerals vary in the resistance to chemical weathering, and the concentrations of Al and Ca provide insights into the relative intensities of mechanical versus chemical weathering. The correlations between Al and Ca concentrations in these two periods, 1000–1550 CE and 1550–1950 CE changed from negative to positive, owing to that agricultural activities evidently enhanced both mechanical and chemical weathering during the latter stage. In addition, the Al and Ca concentrations recorded a border reclamation project in the 16th century and two catastrophic population decreases from 1630s to 1640s and 1850s to 1870s. After 1950 CE, the concentrations of Al and Ca became uncorrelated, because weathering processes around Gonghai Lake were impacted by the enhanced anthropogenic perturbations in the Anthropocene.